Translational Learnings in the Development of Chemo-Immunotherapy Combination to Bypass the Cold Tumor Microenvironment in Pancreatic Ductal Adenocarcinoma - Kaplon, Hélène (Frontiers in Oncology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is among the most lethal cancers, with a 5-year relative survival rate of 5%. The desmoplastic stroma found in the tumor microenvironment of PDAC is suggested to be partly responsible for the resistance to most therapeutic strategies. This review outlines the clinical results obtained with an immune checkpoint inhibitor in PDAC and discusses the rationale to use a combination of chemotherapy and immune checkpoint therapy. Moreover, essential parameters to take into account in designing an efficient combination have been highlighted.